Fish friendly water for agricultural, urban and environmental needs: a California case study - Schild, Neil, author; Cundiff-Gee, Marilyn, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
A project was developed to provide "fish friendly" water for approximately 8,000 acres of wetlands, 8,000 acres of agricultural land, urban water users, and millions of migrating waterfowl. The confluence of Big Chico Creek, and the Sacramento River, is north of the San Francisco Bay/Sacramento-San Joaquin River Delta area. Big Chico Creek once supported healthy runs of chinook salmon and steelhead trout. In the early 1900s, five large pumps were installed on Big Chico Creek, with a combined capacity to divert, for irrigation purposes, about 135 cubic feet per second (CFS) of water. Later, these same pumps were also used to provide water for about 8,000 acres of refuge wetlands on State and Federal wildlife areas. When the pumps were in operation during low flow periods, the unscreened diversion caused stream flow reversals during out migration periods, resulting in a substantial loss of downstream migrants. Due to the loss of winter run salmon, the California Department of Fish and Game and the U.S. Fish and Wildlife Service elected not to exercise their legal right to use the pump station, thus limiting their ability to manage and maintain the critical wetlands. For many years, biologists have called for the removal of the pumps, however, the private landowners did not have $4.5 million necessary to move and screen the pumps. Identifying mutual areas of interest and the multiple benefits associated with this project led to the formation of a partnership consisting of stakeholders that more often than not, were polarized and against one another, i.e., environmental, agricultural and urban water interests. Because of the partnership, the following benefits were achieved: $4.5 million was raised to move the pumps; agricultural operations will continue, fisheries will not be affected, and wetlands will again provide critical habitat for other threatened and endangered species and millions of migrating waterfowl.
1996 USCID water management conference
Not digitized by CSUL Digital Services.
Presented at Competing interests in water resources - searching for consensus: proceedings from the USCID water management conference held on December 5-7, 1996 in Las Vegas, Nevada.